Green Lean Six Sigma critical barriers: exploration and investigation for improved sustainable performance. (3rd November 2021) - Yadav, Vishwas; Gahlot, Pardeep; Kaswan, Mahender Singh; Rathi, Rajeev
Sustainability adoption in manufacturing methods has become the most vital aspect for industrial organisations to sustain in the business run. Green Lean Six Sigma (GLS) is a novel strategy that not only improves green performance but also leads to improve the financial stability of the industries. The present study deals with the identification and analysis of the GLS performance improvement barriers and further prioritises the same using an advanced decision-making approach: best worst method (BWM). Sixteen barriers of GLS have been identified from the literature and further grouped into six critical barriers using principal component analysis (PCA) based on the experts' opinions from industrial personnel. It has found that management and financial constraints with BWM weighted scores 0.4573 and 0.2164, respectively are the most critical barriers. The present study outcome will enhance the knowledge base of researchers and facilitates practitioners to implement GLS through comprehensive understanding and removal of adoption barriers.